PWE-207 Bile duct leaks from an aberrant duct of Luschka. (28th May 2012) - Thayalasekaran, S; Gibson, M; Kinchen, J; Booth, J; Booth, M; Mee, A
Abstract : Introduction: The Duct of Luschka is an accessory biliary radicle first described by the German anatomist Hubert von Luschka in the 19th century. If this aberrant duct goes unnoticed at the time of cholecystectomy, the patient is likely to develop a biliary leak post-operatively. The majority of post-operative leaks are from the cystic duct remnant and standard management is ERCP and stent insertion across the cystic duct +/-sphincterotomy. The aim of our study was to identify the number of leaks from an aberrant "Duct of Luschka" in patients who underwent laparoscopic cholecystectomy over a 14-year period and to evaluate the efficacy of ERCP in their management. Methods: This retrospective study included all patients undergoing cholecystectomy between 1994 and 2010. Those who had a subtotal cholecystectomy were excluded. ERCP reports were reviewed to identify the number of biliary leaks. The medical notes of each patient with an aberrant duct leak were reviewed to evaluate their management. Results: For 5221 laparoscopic cholecystectomies there were 97 biliary leaks (1.9%), 86 from the cystic duct remnant and 11 from an aberrant duct. In two patients found to have leaks from a Duct of Luschka during surgery, the laparoscopic approach was converted to an open procedure and one patient had a drain inserted at initial laparoscopy. Eight patients had a repeat laparoscopy with a washout and drain insertion. Two patients had CT guided drain insertion. Time to ERCP after presentation varied from 1 to 10 days, with the majority being done between day two and day five. Of the eleven, four patients had a sphincterotomy and stent insertion, five had stent insertion alone and two patients had no therapeutic intervention as the leak was felt to be too small. Eight patients had a repeat ERCP with stent removal and no residual leak on cholangiogram. One person was lost to follow-up. No patients required surgery after ERCP to control the leak. Arrow below: leaking aberrant Duct of Luschka. Conclusion: In this study the likelihood of a post cholecystectomy bile leak arising from an aberrant duct of Luschka was 13%, in keeping with previous smaller series where the rate ranged from 0% to 21%. The standard managment with stent insertion +/− sphincterotomy appears to be effective even though the leak is not covered by the stent, presumably by providing preferential drainage. Competing interests: None declared. References: 1.Tantia O, Jain M, Khanna S, et al. Iatrogenic biliary injury. Surg Endosc 2008;22 :1077–86. 2. Sharma H, Bird G. Endoscopic management of postcholecystectomy biliary leaks. Frontline Gastroenterol 2011;2 :230–3. 3. Bartofi J, Baranya F, Simon E, et al. [Laparoscopic treatment of bile leakage from the Luschka Duct after laparoscopic cholecystectomy]. Orv Hetil 2004;145 :1061–4.